Targeting Tumor Initiating Cells through Inhibition of Cancer Testis Antigens and Notch Signaling: A Hypothesis. (4th March 2015) - Colombo, Michela; Mirandola, Leonardo; Reidy, Adair; Suvorava, Natallia; Konala, Venu; Chiaramonte, Raffaella; Grizzi, Fabio; Rahman, Rakhshanda Layeequr; Jenkins, Marjorie R.; Nugyen, Diane D.; Dalhbeck, Scott; Cobos, Everardo; et al.
<x xml:space="preserve">Abstract</x> Tumor initiating cells (TICs) differ from normal stem cells (SCs) in their ability to initiate tumorigenesis, invasive growth, metastasis and the acquisition of chemo and/or radio-resistance. Over the past years, several studies have indicated the potential role of the Notch system as a key regulator of cellular stemness and tumor development. Furthermore, the expression of cancer testis antigens (CTA) in TICs, and their role in SC differentiation and biology, has become an important area of investigation. Here, we propose a model in which CTA expression and Notch signaling interacts to maintain the sustainability of self-replicating tumor populations, ultimately leading to the development of metastasis, drug resistance and cancer progression. We hypothesize that Notch–CTA interactions in TICs offer a novel opportunity for meaningful therapeutic interventions in cancer.